Effects of statins on the c-reactive protein of dyslipidemic patients in the university of Port-Harcourt teaching hospital - Egboh, Stella-Maris C.; Siminialayi, Iyeopu M. (International Journal of Research in Medical Sciences, 2018)
Background: Dyslipidemia is a modifiable cardiovascular risk factor associated with systemic inflammation and can be assessed with a recognized bio-marker known as C-reactive protein. Methods: This was a cohort study carried out over a period of 9 months, where subjects who had abnormality in any of the fasting lipid parameters were recruited into the study, all the subjects had their C-reactive protein assessed, the test subjects were commenced on statins while the control subjects were not on statins and they were all followed up for a period of 3 months after which C-reactive protein was re-assessed. Results: Total 320 subjects were recruited, comprising of 160 test subjects and 160 control subjects. The mean age± SD of the test subjects was 57.02±12.45, while the control subjects had 51.86±13.27 as their mean age± SD. Statins had a significant effect on the reduction of C-reactive protein (p=0.001). Although, there was no correlation between the dosages of statins and its effect on C-reactive protein. Conclusions: Statins were found to have anti-inflammatory effects, although there was no significant correlation between the dosages of statins and their effect on c-reactive protein.